Configuration and evolution of the model of habitation management in chile and colombia (2006)
The following article approaches to the configuration and evolution of lodgment policy in some Latin American scenarios, particularly in Chile and Colombia, reviewing in it’s development the implications of the transformations of the economic models in force between 1950 and 2002 (evolution of the economic model and the State role), the urbanization process and the economic sustainability of the welfare state. Such evolution suggests a review of the housing problem definition as a public policy (both economic and social) from the post-war period (Keynesian economics logic) to the end of the 20th century, in a free market economics logic and a subsidiary role from the State (housing policy aimed at the market with financial assistance –subsidies– to the demand). The question that justifies this article is: Which are the implications of the State involvement in the development and configuration of the housing administration according to the economic ideology in force in the second half of the XXth century? It is to be noted that the studied scenarios adopted administration models that would aid to argument the benefits coverage with a system that guarantied the efficiency in the assignment of the public resources and the economic sustainability of the State’s assistance.